Retinal changes as evidenced by fundoscopy and their frequencies in patients with COVID-19 with different variants of the angiotensin-converting enzyme gene - Hutsaliuk, K. M.; Rossokha, Z. I.; Skalska, N. Iu.; Ulianova, N. A. (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To evaluate the relationship between angiotensin-converting enzyme (ACE; rs4340) gene variants and the retinal changes as evidenced by fundoscopy in patients with various clinical courses of COVID-19. Material and Methods: Ninety-four COVID-19-positive patients (188 eyes) were included in the study. They had an extremely severe course, severe course, or moderately severe course of the disease with decompensated or compensated comorbidity. We evaluated the distribution of ACE ACE genotypes among patients and determined the retinal changes in COVID-19 patients with different ACE genotypes. Fundus images were obtained with a handheld fundus camera to identify clinically significant and insignificant retinal changes. A molecular and genetic study of ACE gene (rs4340) variants was carried out using allele-specific polymerase chain reaction (PCR). Statistical analysis of correlations between the course of COVID-19 and the presence of retinal changes as well as between the ACE gene variant and the presence of retinal changes was conducted. Results: Among the analyzed individuals, 28 (29.6%), 47 (50.5%) and 19 (19.9%) were found to have the II genotype, ID genotype, and DD genotype, respectively. We found no significant correlation between metabolic status, severity of COVID-19 course and the ACE gene variant. No significant difference was found among groups of COVID-19 patients of different ACE genotypes with respect to the distribution of particular retinal changes. There was an increase (p < 0.001) in the risk of clinically significant retinal changes in patients with the DD genotype compared to patients with the II genotype and those with the ID genotype (p < 0.05). Conclusion: The risk of clinically significant retinal changes is higher in COVID-19 patients with ACE genotype DD than in those with genotype II or ID (p < 0.001).